Ischemic Colitis During Pegylated Interferon-Alpha and Ribavirin Therapy for Chronic Hepatitis C - Yvette Leung; Stefan J Urbanski; Lynn Schindel; Robert P Myers (Canadian Journal of Gastroenterology)
Rare cases of ischemic colitis associated with interferon-alpha (IFN-α) treatment for chronic hepatitis C (HCV) infection and metastatic cancer have been reported. The present study describes the first case of ischemic colitis attributable to pegylated IFN-α and ribavirin combination therapy in an HCV-infected patient after 34 weeks of treatment. The clinical presentation, endoscopic appearance and histopathology of the colon were consistent with ischemic colitis, and the patient’s symptoms rapidly resolved with cessation of therapy. The association between the therapy and the pathogenesis of ischemic colitis is unclear, but immunoregulatory, vasospastic and procoagulant mechanisms have been proposed. Physicians should be aware of this complication, and should consider it in any HCV-infected patient taking pegylated IFN-α and ribavirin who develops abdominal discomfort and gastrointestinal bleeding.